Degradable cell patch platform based on two-dimensional silylene nanosheet as well as preparation method and application of degradable cell patch platform

By loading basic copper carbonate nanoparticles and electrostatically modifying human serum albumin onto two-dimensional silicene nanosheets, the problems of degradation and uncontrollable drug release of existing nanomaterials in tumor treatment were solved, realizing intelligent drug release and efficient treatment in the tumor microenvironment.

CN121102494APending Publication Date: 2025-12-12THE SECOND AFFILIATED HOSPITAL OF GUANGZHOU MEDICAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511305395.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-12
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing two-dimensional nanomaterials have problems in tumor treatment, such as poor biodegradability, uncontrollable drug release, low loading efficiency, and lack of responsiveness to the tumor microenvironment, which leads to long-term toxicity and poor treatment effects caused by drug burst release or residual carrier.

Method used

A biodegradable cell patch platform based on two-dimensional silicene nanosheets was adopted. Basic copper carbonate nanoparticles were grown in situ on the surface of the silicene nanosheet matrix and human serum albumin was electrostatically modified to achieve intelligent drug release and tumor targeting, combined with controllable degradation behavior and drug release kinetics.

Benefits of technology

This technology enables rapid degradation and release of drugs in the tumor microenvironment, enhancing the uptake and killing effect on tumor cells, while avoiding premature degradation in the normal physiological environment, thus improving the precision and safety of treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121102494A_ABST
    Figure CN121102494A_ABST
Patent Text Reader

Abstract

The invention belongs to the cross technical field of nanometer materials and biomedicine, and particularly relates to a degradable cell patch platform based on two-dimensional silylene nanosheets and a preparation method and application of the degradable cell patch platform. Comprising a silylene nanosheet substrate, a basic cupric carbonate nanoparticle load and a surface modifier, the thickness of the silylene nanosheet is 1 nm-10 nm, the transverse size of the silylene nanosheet is 300-600 nm, basic cupric carbonate nanoparticles are loaded on the surface of the substrate in an in-situ growth mode, and the load rate of the basic cupric carbonate nanoparticles is 2 wt.%-30 wt.%; and the surface of the matrix is modified with a surface modifier human serum albumin. The surface of the silylene nanosheet matrix is modified and loaded with the basic copper carbonate nanoparticles and the human serum albumin, multifunctional integration is achieved, the patch can be efficiently attached to a cell membrane, the loaded substance is slowly released in the degradation process, the uptake and killing effects of tumor cells are remarkably enhanced, meanwhile, long-term biotoxicity is avoided, and the patch has a good application prospect. The invention is suitable for targeted drug delivery and tumor treatment.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of nanomaterials and biomedical science, and particularly relates to a degradable cell patch platform based on two-dimensional silicene nanosheets as well as a preparation method and application thereof. BACKGROUND

[0002] In recent years, nanomedicine carriers have shown great potential in the field of tumor treatment. By enhancing drug targeting, prolonging circulation time and reducing toxic side effects, the treatment effect has been significantly improved. However, traditional nanocarriers such as liposomes and polymer micelles still have the following limitations: (1) uncontrollable degradation behavior, leading to drug burst release or residual carriers causing long-term toxicity; (2) low loading efficiency, making it difficult to achieve stable encapsulation of high-dose drugs; (3) lack of intelligent response to tumor microenvironment (such as pH and enzyme activity), limiting the application of precise treatment.

[0003] Two-dimensional nanomaterials such as graphene and molybdenum disulfide are widely used for drug loading and delivery due to their high specific surface area and unique physicochemical properties. However, these materials generally have poor biodegradability, and their degradation products can accumulate in the body and cause inflammatory reactions. For example, long-term retention of graphene can cause tissue fibrosis, and molybdenum ions produced by the degradation of molybdenum disulfide are cytotoxic at high concentrations. In addition, existing surface modification strategies for two-dimensional materials focus on functionalization, but do not fully combine their degradation characteristics with drug control requirements, making it difficult to balance carrier efficiency and safety.

[0004] Silicene, as a new type of two-dimensional silicon-based material, has the potential to be used as a biomedical platform due to its biocompatible degradation product, silicic acid (SiO3 2- ). The product silicic acid can be metabolized and excreted by the kidneys, and has no significant toxicity to normal tissues within a certain concentration range. However, due to its uncontrollable degradation rate, it can easily disintegrate rapidly in a physiological environment, leading to premature drug release. SUMMARY

[0005] The purpose of the present application is to provide a degradable cell patch platform based on two-dimensional silicene nanosheets as well as a preparation method and application thereof. The platform can efficiently load drugs and achieve intelligent release in the tumor microenvironment while avoiding long-term biological toxicity.

[0006] The present application solves the above technical problems through the following technical solutions.

[0007] The first object of the present application is to provide a two-dimensional silicene nanosheet-based degradable cell patch platform, which comprises a silicene nanosheet substrate, a basic copper carbonate nanoparticle load, and a surface modifier, wherein the thickness of the silicene nanosheet is 1-10 nm, the lateral size is 300-600 nm, the basic copper carbonate nanoparticles are in situ grown on the surface of the substrate, the loading rate of the basic copper carbonate nanoparticles is 2-30 wt.%, and the surface of the substrate is modified with the surface modifier human serum albumin.

[0008] Further, the content of silicon element in the silicene nanosheet substrate is 20-60 wt.%.

[0009] Further, the degradation rate of the silicene nanosheet substrate in a buffer solution with a pH of 5.5-8.5 within 24 h is 30-90%.

[0010] The second object of the present application is to provide a preparation method of the above-mentioned two-dimensional silicene nanosheet-based degradable cell patch platform, which comprises the following steps: S1. A redox reaction is performed at room temperature using calcium disilicide and iodine as raw materials to obtain silicene, the silicene is dispersed in a solvent, and ice bath ultrasonic exfoliation is performed to obtain a silicene nanosheet dispersion.

[0011] S2. The silicene nanosheet is dispersed in a mixed solvent, then copper sulfate pentahydrate and sodium carbonate are sequentially added, and in-situ growth reaction is performed at room temperature under stirring to load basic copper carbonate nanoparticles on the surface of the silicene nanosheet to obtain a Cu@Si composite material.

[0012] S3. Human serum albumin solution is added to the Cu@Si composite material, and surface electrostatic adsorption modification is performed at room temperature under stirring to obtain the two-dimensional silicene nanosheet-based degradable cell patch platform.

[0013] Further, the molar ratio of calcium disilicide to iodine is 1:1, and the time of the redox reaction is 1-3 weeks.

[0014] Further, the power of the ice bath ultrasonic exfoliation is 800-1000 W, the time is 8-16 h, and the concentration of the silicene nanosheet dispersion is 0.1-1.0 mg / mL.

[0015] Further, the mass ratio of the silicene nanosheet to copper sulfate pentahydrate is 1:1-3, the molar ratio of sodium carbonate to copper sulfate pentahydrate is 1-2:1, and the time of the in-situ growth reaction is 8-24 h.

[0016] Further, the mass ratio of human serum albumin to the Cu@Si composite material in the human serum albumin solution is 1:3-7, and the time of the surface modification is 2-6 h.

[0017] The third object of the present application is to provide an application of the above-mentioned two-dimensional silicene nanosheet-based degradable cell patch platform in the preparation of tumor treatment drugs.

[0018] Compared with the prior art, the present application has the following beneficial effects: The two-dimensional silicene nanosheet-based degradable cell patch platform provided by the present application has a controllable two-dimensional structure and a high specific surface area, and can be gradually degraded into a biocompatible product, silicic acid (SiO3 2- ), in a physiological environment, by loading basic copper carbonate nanoparticles on the surface of the silicene nanosheet substrate through an in-situ growth method, with a copper element loading rate of 2wt.% to 30wt.% and a silicon element content of 10wt.% to 50wt.%. The degradation product of the silicene nanosheet substrate is silicic acid, and the degradation rate is negatively correlated with pH. The intelligent release of copper ions is achieved through the controllable degradation of silicene nanosheets. Copper ions produce reactive oxygen species (ROS) through Fenton reaction to directly kill tumor cells, and the degradation product silicic acid can be metabolized by the kidneys to avoid long-term toxicity. This feature enables the silicene nanosheet to rapidly degrade in the tumor microenvironment, release the loaded drug, and avoid premature degradation in the normal physiological environment, thereby enhancing the uptake and killing effect of tumor cells. At the same time, by electrostatic adsorption of human serum albumin (HSA) on the surface of silicene, the cell membrane targeting property can be enhanced, the tumor cell membrane affinity can be enhanced, and the accumulation efficiency of copper ions at the lesion site can be improved, while the degradation rate of silicene can be regulated, so as to accurately regulate the degradation behavior and drug release kinetics of silicene, ensuring efficient preparation and application of the platform, while avoiding long-term biological toxicity. BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 An electron microscope result graph of the multi-layer stacked silicene of the present application.

[0020] Figure 2 An electron microscope result graph of the silicene of the present application.

[0021] Figure 3 A transmission electron microscope result graph of the basic copper carbonate loaded in Example 1 of the present application.

[0022] Figure 4 A transmission electron microscope result graph of the basic copper carbonate loaded in Example 2 of the present application.

[0023] Figure 5 A transmission electron microscope result graph of the basic copper carbonate loaded in Example 2 of the present application.

[0024] Figure 6 A degradation graph of the silicene nanosheet in Example 1 of the present application in different pH PBS at different time periods.

[0025] Figure 7 TEM images of the silicene nanosheets of Example 1 of the present application after 24 hours at pH = 5.5.

[0026] Figure 8 Cell toxicity chart of Cu@Si and Si of Example 1 of the present application.

[0027] Figure 9 Potential change chart of 2-Cu@Si composite material prepared in Example 3 of the present application and 2-Cu@Si-HSA prepared by 2-Cu@Si.

[0028] Figure 10 Microscope images of 1-Cu@Si-HSA, 2-Cu@Si-HSA and Silicene prepared in the present application after 8h and 22h of co-incubation with cells.

[0029] Figure 11 Scanning electron microscope images of Cu@Silicene-HSA prepared by 1-Cu@Si of the present application after co-incubation with cells. Figure 11 Figure a is a scanning electron microscope image after co-incubation, figure b is that the yellow represents the silicon element attached to the cell surface, and figure c is the element distribution chart of figure b. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.

[0031] Silicene, as a new type of two-dimensional silicon-based material, has become a very potential biomedical platform due to its property of degrading into biocompatible product silicic acid (SiO3 2- However, due to its uncontrollable degradation rate, it is easy to disintegrate rapidly in a physiological environment, resulting in premature drug release. In addition, the preparation process of silicene in the prior art is complex, the yield is low, and there is a lack of systematic study on the degradation kinetics and drug release behavior of silicene, and no targeting modification is introduced, which cannot achieve tumor-specific accumulation. Therefore, developing a degradable nanoplatform based on silicene, by precisely regulating its degradation behavior and drug release kinetics, and combining with surface targeting modification to enhance tumor selectivity, has become the key to solving the above technical bottlenecks.

[0032] Based on this, on the one hand, the present invention provides a biodegradable cell patch platform based on two-dimensional silicene nanosheets. The biodegradable cell patch platform includes a silicene nanosheet matrix, a basic copper carbonate nanoparticle loading material, and a surface modifier. The silicene nanosheets have a thickness of 1 nm to 10 nm and a lateral dimension of 300 to 600 nm. The basic copper carbonate nanoparticles are grown in situ and loaded on the surface of the matrix, with a loading rate of 2 wt.% to 30 wt.%. The matrix surface is modified with a surface modifier, which is human serum albumin.

[0033] The silicene nanosheet matrix provided by this invention has a controllable two-dimensional structure and a high specific surface area, and can be gradually degraded into the biocompatible product silicic acid (SiO3) under physiological conditions. 2- Basic copper carbonate nanoparticles were loaded onto the surface of a silicene nanosheet substrate via in-situ growth. The copper loading rate was 2%–30%, and the silicon content was 10 wt.%–50 wt.%. The degradation product of the silicene nanosheet substrate was silicic acid. In a buffer solution with a pH of 5.5–8.5, the degradation rate was 30%–90% within 24 hours, and the degradation rate was negatively correlated with pH. The controlled degradation of the silicene nanosheets enabled the intelligent release of copper ions. These copper ions generated reactive oxygen species (ROS) through the Fenton reaction, directly killing tumor cells. Simultaneously, the degradation product silicic acid could be metabolized by the kidneys, avoiding… The long-term toxicity of silicene nanosheets allows them to rapidly degrade in the tumor microenvironment, releasing the loaded drug while avoiding premature degradation in normal physiological environments, thus enhancing the uptake and killing effect on tumor cells. Furthermore, by electrostatically adsorbing and modifying the silicene surface with human serum albumin (HSA), cell membrane targeting and tumor cell membrane affinity can be enhanced, increasing the accumulation efficiency of copper ions at the lesion site. Simultaneously, the degradation rate of silicene can be regulated, thereby precisely controlling the degradation behavior of silicene and drug release kinetics, ensuring the efficient preparation and application of the platform while avoiding long-term biotoxicity.

[0034] In some embodiments, the silicon content of the silicene nanosheet matrix is ​​20 wt.% to 60 wt.%.

[0035] On the other hand, the present invention also provides a method for preparing a biodegradable cell patch platform based on two-dimensional silicene nanosheets, comprising the following steps: S1. Add the first solvent to calcium disilicide and iodine, and carry out a redox reaction at room temperature. After the reaction is completed, centrifuge to obtain the centrifuged product silicene. Disperse the centrifuged product silicene in the second solvent and perform ice bath ultrasonic exfoliation to obtain a silicene nanosheet dispersion.

[0036] S2. Disperse silicene nanosheets in a mixed solvent, then add copper sulfate pentahydrate and sodium carbonate in sequence, and stir at room temperature to carry out an in-situ growth reaction, so that basic copper carbonate nanoparticles are loaded on the surface of the silicene nanosheets to obtain Cu@Si composite material.

[0037] S3. Add human serum albumin solution to Cu@Si composite material and stir at room temperature to perform surface electrostatic adsorption modification to obtain a biodegradable cell patch platform based on two-dimensional silicene nanosheets.

[0038] This invention employs a chemical exfoliation method to prepare silicene nanosheets. The preparation process is simple and yields high output, resulting in silicene nanosheets with a controllable two-dimensional structure and high specific surface area. These nanosheets can be progressively degraded into the biocompatible product silicic acid under physiological conditions. Then, basic copper carbonate nanoparticles are loaded onto the surface of the silicene nanosheets via in-situ growth, and serum albumin (HSA) is modified by electrostatic adsorption, achieving multifunctional integration. The degradation rate can be precisely controlled by adjusting the oxygen and moisture content, salt solution concentration, and pH of the environment. By loading functional components onto the controllably degradable silicene nanosheets and combining them with surface-targeted modification, intelligent drug delivery and synergistic therapy in response to the tumor microenvironment can be achieved. The degradation behavior of silicene and drug release kinetics can be precisely regulated, ensuring the efficient preparation and application of the platform.

[0039] In some embodiments, the molar ratio of calcium disilicide to iodine is 1:1, and the redox reaction time is 1 to 3 weeks. In a preferred embodiment, the first solvent is anhydrous acetonitrile, the centrifugation speed is 8000 rpm to 12000 rpm, after centrifugation, the supernatant containing calcium iodide is discarded, and the precipitate is washed three times with anhydrous acetonitrile to obtain the centrifuged product.

[0040] In some embodiments, the power of the ice bath ultrasonic exfoliation is 800W to 1000W, the time is 8h to 16h, and the concentration of the silicene nanosheet dispersion is 0.1mg / mL to 1.0mg / mL. In a preferred embodiment, the second solvent is 1-methyl-2-pyrrolidone. After the ice bath ultrasonic exfoliation is completed, the mixture is centrifuged at 1000rpm for 30min, and the supernatant is collected to obtain the silicene nanosheet dispersion, which is stored at 4℃ for later use.

[0041] In some embodiments, the mass ratio of silicene nanosheets to copper sulfate pentahydrate is 1:1 to 3, the molar ratio of sodium carbonate to copper sulfate pentahydrate is 1 to 2:1, and the in-situ growth reaction time is 8 h to 24 h. In a preferred embodiment, the mixed solvent is a mixture of ethylene glycol and ethanol. After the in-situ growth reaction is completed, the precipitate is collected by centrifugation, washed three times successively with deionized water and ethanol, and dispersed in ethanol for later use.

[0042] In some embodiments, the mass ratio of human serum albumin to Cu@Si composite material in the human serum albumin solution is 1:3 to 7, and the surface modification time is 2 to 6 hours. In a preferred embodiment, after surface modification, unbound HSA is removed by centrifugation, and the precipitate is washed three times with PBS.

[0043] The present invention also provides the application of the above-mentioned biodegradable cell patch platform based on two-dimensional silicene nanosheets in the preparation of tumor therapeutic drugs.

[0044] The following specific examples will provide further explanation.

[0045] Example 1 A method for preparing Cu@Si composite material includes the following steps: S1. Preparation of silicene nanosheets: Weigh 1.725 g of calcium disilicide (CaSi2) and 4.572 g of iodine (I2), add them to 240 mL of anhydrous acetonitrile, and stir at room temperature for 2 weeks under argon protection. After the reaction, centrifuge at 11000 rpm for 30 min, discard the supernatant containing CaI2, and wash the precipitate three times with anhydrous acetonitrile. Disperse the precipitate in 150 mL of N-methylpyrrolidone (NMP), and treat with an ultrasonic probe at 900 W for 12 h in an ice bath. After the reaction, centrifuge at 1000 rpm for 30 min, collect the supernatant to obtain a silicene nanosheet dispersion, and store it at 4℃ for later use.

[0046] Preparation of S2, Cu@Si composite materials: Silica nanosheets were obtained by drying the silica nanosheet dispersion. 30 mg of silica nanosheets were weighed and dispersed in 50 mL of ethanol, and sonicated for 30 min. Then, 30 mg of copper sulfate pentahydrate (CuSO4·5H2O) was dissolved in 50 mL of ethylene glycol and slowly added dropwise to the silica nanosheet dispersion. The mixture was stirred at 500 rpm for 12 h. Finally, 8.25 mg of sodium carbonate (Na2CO3) was added. 3, Dissolve in 10 mL of ethylene glycol and continue stirring for 12 h. After the reaction is complete, centrifuge to collect the precipitate, and wash it three times with deionized water and ethanol to obtain the Cu@Si composite material, named 1-Cu@Si.

[0047] Example 2 A method for preparing Cu@Si composite material includes the following steps: S1. Preparation of silicene nanosheets: Weigh 1.725 g of CaSi2 and 4.572 g of I2, add them to 240 mL of anhydrous acetonitrile, and stir at room temperature for 2 weeks under argon protection. After the reaction, centrifuge at 11000 rpm for 30 min, discard the supernatant containing CaI2, and wash the precipitate three times with anhydrous acetonitrile. Disperse the precipitate in 150 mL of NMP, and treat it with an ultrasonic probe at 900 W for 12 h in an ice bath. After the reaction, centrifuge at 1000 rpm for 30 min, collect the supernatant to obtain the silicene nanosheet dispersion, and store it at 4℃ for later use.

[0048] Preparation of S2, Cu@Si composite materials: Silica nanosheets were obtained by drying the silica nanosheet dispersion. 30 mg of silica nanosheets were weighed and dispersed in 50 mL of ethanol, and sonicated for 30 min. Then, 90 mg of CuSO4·5H2O was dissolved in 50 mL of ethylene glycol and slowly added dropwise to the silica nanosheet dispersion. The mixture was stirred at 500 rpm for 12 h. Finally, 24.75 mg of sodium carbonate (Na2CO3) was added. 3, Dissolve in 10 mL of ethylene glycol and continue stirring for 12 h. After the reaction is complete, centrifuge to collect the precipitate, and wash it three times with deionized water and ethanol to obtain the Cu@Si composite material, named 3-Cu@Si.

[0049] Example 3 A method for preparing Cu@Si composite material includes the following steps: S1. Preparation of silicene nanosheets: Weigh 1.725 g of CaSi2 and 4.572 g of I2, add them to 240 mL of anhydrous acetonitrile, and stir at room temperature for 2 weeks under argon protection. After the reaction, centrifuge at 11000 rpm for 30 min, discard the supernatant containing CaI2, and wash the precipitate three times with anhydrous acetonitrile. Disperse the precipitate in 150 mL of NMP, and treat it with an ultrasonic probe at 900 W for 12 h in an ice bath. After the reaction, centrifuge at 1000 rpm for 30 min, collect the supernatant to obtain the silicene nanosheet dispersion, and store it at 4℃ for later use.

[0050] Preparation of S2, Cu@Si composite materials: Silica nanosheets were obtained by drying the silica nanosheet dispersion. 30 mg of silica nanosheets were weighed and dispersed in 50 mL of ethanol, and sonicated for 30 min. Then, 60 mg of CuSO4·5H2O was dissolved in 50 mL of ethylene glycol and slowly added dropwise to the silica nanosheet dispersion. The mixture was stirred at 500 rpm for 12 h. Finally, 16.5 mg of sodium carbonate (Na2CO3) was added. 3, Dissolve in 10 mL of ethylene glycol and continue stirring for 12 h. After the reaction is complete, centrifuge to collect the precipitate, and wash it three times with deionized water and ethanol to obtain the Cu@Si composite material, named 2-Cu@Si.

[0051] The structure and morphology of the Cu@Si composite materials prepared in Examples 1 to 3 were tested, and the results are as follows: Transmission electron microscopy (TEM) was used to observe the morphology of the preserved silicene nanocell patch samples. The samples were dispersed in water and dropped onto a clean copper grid. TEM allowed for direct observation of the two-dimensional sheet-like structure of the silicene nanosheets and the uniform distribution of copper nanoparticles on the silicene surface.

[0052] Figure 1 This is an electron microscope image of the initial silicene nanosheets of this invention. Figure 1 As shown, without water bath ultrasonic ablation, it exhibits a microstructure resembling an accordion shape.

[0053] Figure 2 This is an electron microscope image of the silicene nanosheets prepared in Example 1 of the present invention. Figure 2 As shown, monolayer or few-layer silicene nanosheets with a diameter of about 300 nm to 500 nm were prepared by chemical exfoliation, resulting in silicene nanosheets with a controllable two-dimensional structure and high specific surface area.

[0054] Figure 3 The image shows the electron microscope results of the Cu@Si composite material prepared in Example 1 of this invention. Figure 3 As shown, at this time, a small amount of basic copper carbonate nanoparticles in 1-Cu@Si are loaded on the surface of silicene.

[0055] Figure 4 The image shows the electron microscope results of the Cu@Si composite material prepared in Example 2 of this invention. Figure 4 As shown, when basic copper carbonate mineralizes and encapsulates silicene nanosheets, the loading rate increases, but the degradability of the silicene nanosheets decreases, reducing the contact area between silicene and the cell membrane.

[0056] Figure 5 The image shows the electron microscope results of the Cu@Si composite material prepared in Example 3 of this invention. Figure 5 As shown, basic copper carbonate is uniformly loaded onto the silicene nanosheets, ensuring sufficient contact area between the silicene and oxygen, as well as the solution, thus guaranteeing good degradability. ICP-OES analysis revealed a Cu loading rate of 20.3 wt.% and a silicon content of 33.5 wt.%.

[0057] The silicene nanosheets prepared in Example 1 were dispersed in PBS buffer (concentration 25 μg / mL) at pH 5.5, 6.5, and 7.4. Real-time images of the liquid were observed at 0 h, 2 h, 4 h, 8 h, 12 h, and 24 h. Figure 6 This is a graph showing the degradation of silicone nanosheets in PBS at different pH values ​​and at different time periods in Example 1 of the present invention. Figure 6As shown, significant degradation is observed at pH 5.5. Transmission electron microscopy was used to identify whether the silicone sheets had degraded. Figure 7 This is a transmission electron microscope (TEM) image of the silicene nanosheets from Example 1 of the present invention after 24 hours at pH 5.5. Figure 7 As shown, the silicene sheet has undergone significant degradation.

[0058] Cytotoxicity evaluation: The cytotoxicity of the material was assessed using the MTT assay (thiazolyl blue assay). 4T1 cells were cultured at a rate of 8 × 10⁶ cells / year. 3 Cells were seeded at a density of 100 μL per well in 96-well cell culture plates. After the cells adhered and spread completely, the culture medium was aspirated, and free DMEM complete medium containing different concentrations of Silience, Example 1-Cu@Si, and 2-Cu@Si was added to each well for further culture. After 24 hours of incubation, the original culture medium was aspirated, and the cells were washed once with PBS. Then, in addition to adding 100 μL of DMEM medium, 20 μL of MTT solution (5 mg / mL) was added to each well. -1 After incubation for 4 hours, the culture medium was aspirated, and 150 μL of DMSO solution was added to dissolve the blue-purple formazan crystals. Cell viability was then measured using a microplate reader at a wavelength of 570 nm. Figure 8 This is a cytotoxicity diagram of Cu@Si and Si in Example 1 of the present invention. Figure 8 As shown, when the concentration of silicene is ≤120μg / mL, the cell survival rate is >85%, while after loading with basic copper carbonate, the cell survival rate is <38% when the concentration is ≤120μg / mL.

[0059] Based on the Cu@Si composite material prepared above, the Cu@Si composite material is used to prepare a biodegradable cell patch platform based on two-dimensional silicene nanosheets, including the following steps: HSA-modified silicene patches: 20 mg of human serum albumin (HSA) was dissolved in 10 mL of PBS buffer (pH 7.4). 12 mg of 1-Cu@Si prepared in Example 1 or 2-Cu@Si prepared in Example 3 was dispersed in 10 mL of deionized water. The HSA solution was added dropwise, and the mixture was stirred at room temperature for 4 hours. Unbound HSA was removed by centrifugation, and the precipitate was washed three times with PBS to obtain 1-Cu@Si-HSA and 2-Cu@Si-HSA composite patches, which constitute a biodegradable cell patch platform based on two-dimensional silicene nanosheets.

[0060] Figure 9 The potential change diagrams are shown for the 2-Cu@Si composite material prepared in Example 3 of this invention and the 2-Cu@Si-HSA prepared from 2-Cu@Si. Figure 9As shown, the potential of silicene is negative, but it turns positive after loading with basic copper carbonate, confirming the successful loading of basic copper carbonate. After modification with human serum albumin (HSA), the potential turns negative, preliminarily confirming the successful encapsulation of human serum albumin.

[0061] Verification of the cell adhesion effect of silicene: 4T1 cells were arranged at a ratio of 1×10 5 Cells were seeded at a density of 100 cells per well in 24-well cell culture plates. After the cells adhered and spread completely, the culture medium was aspirated, and complete DMEM medium containing Si, 1-Cu@Si-HSA, and 2-Cu@Si-HSA was added to different wells for further culture. After 24 hours of incubation, residual silica material was washed away with PBS, dispersed in water, and then fixed with paraformaldehyde to prepare SEM samples.

[0062] 24-hour cell dynamics monitoring: Complete DMEM medium containing Si, 1-Cu@Si-HSA, and 2-Cu@Si-HSA was added to cells cultured in the logarithmic growth phase and added to different wells for further culture. The adhesion status of the nanopatches was continuously monitored for 24 hours, and the stability of the nanopatches on the cell surface was observed using a blank (Con) as a control.

[0063] Figure 10 The images show the microscopic results of 1-Cu@Si-HSA, 2-Cu@Si-HSA, and silicone after co-incubation with cells for 8 hours and 22 hours, respectively, as prepared in this invention. Figure 10 As shown, silicene patches 1-Cu@Si-HSA and 2-Cu@Si-HSA adhere to the cell surface. After modification, the material's tumor targeting ability is improved due to HAS targeting the G60 receptor protein on the surface of 4T1 cells, resulting in better adhesion.

[0064] Figure 11 The image shows the scanning electron microscope results of Cu@Silicene-HSA prepared by 1-Cu@Si in this invention after co-incubation with cells. Figure 11 Image a shows a scanning electron microscope image after co-incubation; in image b, yellow represents silicon attached to the cell surface; and image c shows the distribution of elements in image b. Figure 11 As shown, the silicene nanosheets, represented by Si, adhere to the cell membrane surface in a sheet-like manner, and some silicene nanosheets show significant degradation, forming scattered silica spheres on the cell surface. The adhesion of the silicene nanosheets to the cell surface was observed using SEM to verify their affinity for the cell membrane.

[0065] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of the invention have been described, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.

[0066] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A biodegradable cell patch platform based on two-dimensional silicene nanosheets, characterized in that, The biodegradable cell patch platform comprises a silicene nanosheet substrate, a basic copper carbonate nanoparticle loading material, and a surface modifier. The silicene nanosheets have a thickness of 1 nm to 10 nm and a lateral dimension of 300 nm to 600 nm. The basic copper carbonate nanoparticles are grown in situ and loaded onto the substrate surface, with a loading rate of 2 wt.% to 30 wt.%. The substrate surface is modified with the surface modifier human serum albumin.

2. The biodegradable cell patch platform based on two-dimensional silicene nanosheets according to claim 1, characterized in that, The silicon content of the silicene nanosheet matrix is ​​20 wt.% to 60 wt.%.

3. The biodegradable cell patch platform based on two-dimensional silicene nanosheets according to claim 1, characterized in that, The degradation rate of silicene nanosheet matrix in buffer solution with pH 5.5–8.5 is 30%–90% within 24 hours.

4. A method for preparing a biodegradable cell patch platform based on two-dimensional silicene nanosheets as described in any one of claims 1 to 3, characterized in that, Includes the following steps: Silene was obtained by redox reaction of calcium disilicide and iodine at room temperature. The silene was dispersed in a solvent and subjected to ultrasonic exfoliation in an ice bath to obtain a silene nanosheet dispersion. Silene nanosheets were dispersed in a mixed solvent, and then copper sulfate pentahydrate and sodium carbonate were added sequentially. The mixture was stirred at room temperature to carry out an in-situ growth reaction, so that basic copper carbonate nanoparticles were loaded on the surface of the silene nanosheets to obtain Cu@Si composite material. Human serum albumin solution was added to Cu@Si composite material, and surface electrostatic adsorption modification was carried out by stirring at room temperature to obtain a biodegradable cell patch platform based on two-dimensional silicene nanosheets.

5. The method for preparing the biodegradable cell patch platform based on two-dimensional silicene nanosheets according to claim 4, characterized in that, The molar ratio of calcium disilicide to iodine is 1:1, and the reaction time is 1 to 3 weeks.

6. The method for preparing the biodegradable cell patch platform based on two-dimensional silicene nanosheets according to claim 4, characterized in that, The power of the ice bath ultrasonic exfoliation was 800W to 1000W, the time was 8h to 16h, and the concentration of the silicene nanosheet dispersion was 0.1mg / mL to 1.0mg / mL.

7. The method for preparing the biodegradable cell patch platform based on two-dimensional silicene nanosheets according to claim 4, characterized in that, The mass ratio of silicene nanosheets to copper sulfate pentahydrate is 1:1 to 3, the molar ratio of sodium carbonate to copper sulfate pentahydrate is 1 to 2:1, and the in-situ growth reaction time is 8 h to 24 h.

8. The method for preparing the biodegradable cell patch platform based on two-dimensional silicene nanosheets according to claim 4, characterized in that, The mass ratio of human serum albumin to Cu@Si composite material in the human serum albumin solution is 1:3 to 7, and the surface modification time is 2h to 6h.

9. The application of the biodegradable cell patch platform based on two-dimensional silicene nanosheets as described in any one of claims 1 to 3 in the preparation of tumor therapeutic drugs.